'Asians' and 'Westerners': examining the perception of '(non-)native' migrant teachers of English in Thailand. Issue 8 (13th September 2020) - Comprendio, Luke Jobert Earl Vencer; Savski, Kristof
ABSTRACT: Existing research has highlighted the complexity of the discourse surrounding '(non-)native speaker', particularly with regard to how teachers are perceived by learners. This complexity has been compounded by globalisation, which has increased transnational mobility of teachers. Thailand has been particularly affected by this, as its population of local teachers has been complemented by a growing yet highly diverse contingent of migrant teachers. In this paper, we present the results of a study conducted at three secondary schools in Southern Thailand, which used a combination of interviews and focus groups to examine how various local participants in English teaching and learning (teachers, students, parents, administrators) perceived migrant (i.e. non-Thai) English teachers, focussing particularly on how these perceptions used '(non-)nativeness' as a point of reference. Our analysis focusses on two overarching themes, 'race' and 'inequality', which also invoke links with broader discourses: Firstly, we show that the perceptions of migrant teachers were heavily racialized, with 'nativeness' equated with whiteness and Westernness and 'non-nativeness' associated with Asianness. Secondly, we find that the participants' perceptions involved significant reference to inequality, as access to 'nativeness' represented a symbolic resource accessible only to learners with sufficient economic capital.